Sifat Mekanik Beton dengan Substitusi Limbah Kaca dan Penambahan SikaCim Concrete Additive - Restu Anggara; Hariyadi Haryadi; Adryan Fitrayudha (Jurnal Talenta Sipil, 2026)
The demand for high-strength concrete in Indonesia continues to grow, yet the exploitation of natural sand as fine aggregate poses a risk of environmental damage, creating a need for alternative materials. This study aims to analyze the effect of glass waste substitution on the mechanical properties of high-strength concrete (design f'c of 40 MPa) with SikaCim Concrete Additive. The method used was a laboratory experiment on cylindrical specimens (10×20 cm) with glass waste substitution for fine aggregate at 0%, 10%, 20%, and 30%, including slump testing, compressive strength testing (Compression Testing Machine), and splitting tensile strength testing at 7, 14, 21, and 28 days. The results showed that compressive strength decreased consistently as the substitution level increased, from 37.66 MPa (normal concrete) to 35.37 MPa (10%), 34.01 MPa (20%), and 33.67 MPa (30%), a decline of up to 10.59%. In contrast, splitting tensile strength followed a non-monotonic pattern: it dropped sharply at 10% substitution (3.56 MPa; a 20.54% decrease), then rose again at 20% (3.74 MPa) and 30% (4.30 MPa), approaching the value of normal concrete (4.48 MPa), with the highest ft/√f'c ratio occurring at 30% substitution (0.741), exceeding that of normal concrete (0.730). It is concluded that within the 0–30% substitution range, glass waste did not produce an optimum point that increased compressive strength above that of normal concrete, but at 30% it provided a relatively better balance between compressive and splitting tensile strength, indicating that the feasibility of using glass waste cannot be assessed from compressive strength alone.